Clinical Profiles of Chronic Kidney Disease Patients at the Time of Maiden Presentation: An Experience at the Nephrology Ward, Chittagong Medical College Hospital (Journal of Chittagong Medical College Teachers' Association, 2011)
Key words: CKD patients; Renam status at maiden presentation; Nephrology ward of CMCHDOI: 10.3329/jcmcta.v21i2.7729 Journal of Chittagong Medical College Teachers' Association 2010: 21(2):7-10